2018
DOI: 10.1021/acsaem.8b01080
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Electrochemical Properties of Spinel Intercalation Compounds

Abstract: Spinel intercalation compounds are well-known to facilitate high rate and high voltage Li-ion batteries. Little is known, however, about spinel based electrodes for Na-and Mg-ion batteries. Here we systematically study six spinel chemistries with first-principles statistical mechanics approaches to determine how the electrochemical properties of spinel compounds are affected by (i) host ionicity, (ii) guest cation radius, and (iii) guest cation oxidation state. As model systems, we consider spinel CoO 2 and Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…In addition to the compositions listed above, we also considered materials that are stable against Mg metal 24,26 (potential anode coatings) and analogous chemistries that have been employed in Li-systems (e.g., Li-Nb oxides). [18][19][20][21][22] Although prior studies have demonstrated [27][28][29][30] that the lack of Mg (or multivalent) mobility in several structures relates to a combination of stronger electrostatic interactions of a 2+ charge with its surrounding anion environment (versus 1+ charge of monovalent ions) and strong coordination preferences, 17,25,[31][32][33][34] Mg mobility has not been rigorously quantified yet for potential coating chemistries.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the compositions listed above, we also considered materials that are stable against Mg metal 24,26 (potential anode coatings) and analogous chemistries that have been employed in Li-systems (e.g., Li-Nb oxides). [18][19][20][21][22] Although prior studies have demonstrated [27][28][29][30] that the lack of Mg (or multivalent) mobility in several structures relates to a combination of stronger electrostatic interactions of a 2+ charge with its surrounding anion environment (versus 1+ charge of monovalent ions) and strong coordination preferences, 17,25,[31][32][33][34] Mg mobility has not been rigorously quantified yet for potential coating chemistries.…”
Section: Introductionmentioning
confidence: 99%
“…Kolli et al, investigated the electrochemical properties of spinel intercalation compounds, in their study it is proved that the guest cation played an important role in determining the electrochemical performance. [55] Also, the inverse spinel showed a higher electrochemical performance due to the occupancy of the trivalent cation in the A site and also partially in the B site,…”
Section: Co-based Bimetallic Oxidesmentioning
confidence: 99%
“…A normal spinel compound transforms into an inverse spinel when the equation is Cu x Co 3-x O with x higher than 0.2. [55] In the inverse spinel CuCo 2 O 4, the Co 3 + cations were distributed to both A sites, and one-half of the B sites, the Cu 2 + cations occupy the B sites. CuCo 2 O 4 showed a high theoretical capacitance of 984 F g À 1 , with a bandgap of 0.5-0.6 eV which shows a good conductivity.…”
Section: Co-based Bimetallic Oxidesmentioning
confidence: 99%
See 2 more Smart Citations